2010
DOI: 10.1080/19376812.2010.9756226
|View full text |Cite
|
Sign up to set email alerts
|

Oil and Armed Conflicts in Africa

Abstract: Popular geopolitical representations of oil in Africa conjure up images of corrupt politicians, disgruntled populations, and predatory foreign oil companies: a volatile mix that would supposedly keep African "petrostates" locked in armed conflicts. This article queries these geopolitical narra, and offers a different perspective: while several countries-such as Algeria, Angola, Nigeria and Sudan-have indeed experienced long and deadly conflicts, African oil-producing countries have not, on average, been more f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Empirically, studies have shown a positive relationship between the revenue from the sales of natural resources and conflicts, especially in developing countries. For example, Le Billon (2010) examined Africa’s oil and armed conflict nexus and found that oil generally motivates and generates the onset of conflict in Africa. Furthermore, Anyanwu (2014) found that African countries endowed with oil but ethnically and linguistically fractionalized are more likely to experience civil conflict.…”
Section: Relevant Literature Reviewmentioning
confidence: 99%
“…Empirically, studies have shown a positive relationship between the revenue from the sales of natural resources and conflicts, especially in developing countries. For example, Le Billon (2010) examined Africa’s oil and armed conflict nexus and found that oil generally motivates and generates the onset of conflict in Africa. Furthermore, Anyanwu (2014) found that African countries endowed with oil but ethnically and linguistically fractionalized are more likely to experience civil conflict.…”
Section: Relevant Literature Reviewmentioning
confidence: 99%
“…The hypotheses in this article are informed by previous research. The more informed citizens are, the less negative they will be about natural resource revenue management (Le Billon, 2007Billon, , 2010Lujala, 2017;Lujala et al, 2020;Musavengane & Siakwah, 2020;Orogun, 2010). Overall, men, the youth, and the more educated seem to be more informed on national issues than women, the aged, and the less educated (Bernal & Vásquez, 2016;Lujala et al, 2020;.…”
Section: Hypothesesmentioning
confidence: 99%
“…Later, as a consequence of shutting down its oil production in its dispute with Sudan, a lack of oil money in South Sudan led to the factionalization of ruling elites and a drawn-out civil war beginning in late 2013 (de Waal, 2014). Unlike other African oil producers, such as Angola, with large offshore oil resources tightly controlled by the central government, the political geography of onshore oilfields, along with its territorial disputes and poor institutions, served to mire Sudan and South Sudan's boom decade in conflict (Le Billon, 2010).…”
Section: Governance Of the Oil Boommentioning
confidence: 99%